Usefulness of Left Atrial Volume in Predicting First Congestive Heart Failure in Patients ≥65 Years of Age With Well-Preserved Left Ventricular Systolic Function - Takemoto, Yasuhiko; Barnes, Marion E.; Seward, James B.; Lester, Steven J.; Appleton, Christopher A.; Gersh, Bernard J.; Bailey, Kent R.; Tsang, Teresa S.M. (The American journal of cardiology, 2005)
Left atrial (LA) volume is a barometer of diastolic dysfunction. Whether it predicts congestive heart failure (CHF) in patients with preserved left ventricular (LV) systolic function is not known. Olmsted County, Minnesota, residents aged ≥65 years referred for transthoracic echocardiography from 1990 to 1998, who were in sinus rhythm without a history of CHF were followed in the medical records to 2003 (mean follow-up duration 4.3 ± 2.7 years). Of the 1,495 patients identified, 1,375 (92%) with LV ejection fractions ≥50% (mean age 75 ± 7 years; 59% women) constituted the study population, 138 (10%) of whom developed CHF. Baseline LA volume ≥32 ml/m 2 was an independent predictor of first CHF (p <0.001). Of the 138 patients who had first CHF, ejection fractions were assessed within 4 weeks of diagnosis in 98 subjects, 74 (76%) of whom had ejection fractions remaining at ≥50%, with a mean increase in LA volume of 8 ± 10 ml/m 2 (p <0.001) from baseline. The age-adjusted CHF-free survival rates for LA volume tertiles (<28, 28 to ≤37, and >37 ml/m 2) were 95%, 91%, and 83%, respectively (p <0.001). In conclusion, LA volume independently predicted first CHF in an elderly cohort with well-preserved LV systolic function.